IMPLEMENTASI PENERAPAN KONVERGENSI IFRS TERHADAP LAPORAN KEUANGAN - Khoirul Anam (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The purpose of this article is to investigate the implementation of IFRS convergence on financial reporting. The author employs a literature review method to collect various sources of literature data, including journals, documents, and books related to the researched topic. The research findings, based on analyzing several articles regarding the implementation of IFRS convergence on financial reporting, show that convergence to IFRS may increase complexity in the concepts of fair value and cash value in measuring assets and liabilities. However, the opportunity and risk can be minimized effectively. Consequently, users of financial reports can make accurate and informed decisions.